Proposal Of A Method For Analysıs Of Lıterary Works In The Fıelds Of Utopıa And Dystopıa - Guner, Barış; Polat, Orhun (Advances in Social Sciences Research Journal, 2017)
Utopian and dystopian works are within the field of sociological works. The said works have a significant place in the explanations of sociology as to society due to their housing a design of a new society within themselves. As such, they are the subject of examination in numerous scientific studies. Objective of this study is to propose an analysis method which can be utilized in the process of examining such literary works penned in the fields of utopia and dystopia and prove the usefulness of the cited method. How the analysis method will be has been determined as methodology in line with this defined objective at the first stage. Then a literary work penned in the fields of utopia and dystopia has been selected. Usefulness of the cited method has been tried to be proven via this work at the final stage. It is possible to evaluate this work through social change components by virtue of this analysis method proposed within the study which facilitates understanding the message the author tries to convey more accurately. Furthermore, it is anticipated that utilization of the proposed analysis method in examination of utopian and dystopian works to be carried out later will enable the comparison of different literary works through the same social changes in a systematic manner.